Kebijakan Badan Kesatuan Bangsa Dan Politik Dompu Dalam Upaya Deradikalisasi Terhadap Mantan Narapidana Terorisme Di Kabupaten Dompu - Muamar; Suparman; Sukarddin (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
Extremism or radicalism is a call for terrorists and their supporters to use violence to achieve certain goals, often based on religious legitimacy. Dompu Regency is one of the places where many convicted terrorists are found. In this context, Bakesbanpol Dompu Regency plays a role in Deradicalization efforts. Deradicalization is a process or effort to eliminate radicalism. The purpose of this study is to describe the Kesbangpol policy in Dompu Regency in efforts to deradicalize ex-convicts in Dompu Regency and to analyze the factors causing obstacles in the implementation of deradicalization of ex-convicts. The methodology used in this study is qualitative descriptive. Efforts to determine and achieve research objectives are carried out using indicators of the role of local government in this case Kesbangpol as a facilitator and as a regulator. The results of the study indicate that the role of the government as a facilitator in the implementation of deradicalization of ex-convicts has been carried out as seen from the form of providing guidance, skills, training and funding given to ex-convicts. While the role of the government as a regulator, currently the local government does not have regional regulations that specifically regulate radicalism, terrorism or even deradicalization. Differences in thinking/ideology, limited budget and labeling from the community towards ex-convicts are obstacles in the implementation of deradicalization of ex-convicts in Dompu Regency. The Regional Government needs to provide religious guidance through religious leaders and additional allocations in the implementation of the program. In addition, the government and the community must be present in the midst of ex-convicts and synergize in preventing radicalism and terrorism.